1996
DOI: 10.1109/87.486345
|View full text |Cite
|
Sign up to set email alerts
|

Control loop performance monitoring

Abstract: Abstruct-Control loop monitoring can be used to improve the performance of processes in industry. The monitoring tools presented are concerned with reducing the output variance of regulation loops; As a result, three different estimators are used to determine the minimum achievable output variance, the time delay and the static input-output relationship of the process. These three properties can be used together or individually to provide insights into the process. Once the methods are introduced and their alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Methodologies for the estimation of the best achievable performance bound in terms of output variance have been established for SISO con-Ž trol systems Harris, 1989;Desborough and Harris, 1992; . Stanfelj et al, 1993;Lynch and Dumont, 1996;Kozub, 1997 Ž and MIMO control systems Harris et al, 1996;Huang et al, . 1997 .…”
Section: Introductionmentioning
confidence: 98%
“…Methodologies for the estimation of the best achievable performance bound in terms of output variance have been established for SISO con-Ž trol systems Harris, 1989;Desborough and Harris, 1992; . Stanfelj et al, 1993;Lynch and Dumont, 1996;Kozub, 1997 Ž and MIMO control systems Harris et al, 1996;Huang et al, . 1997 .…”
Section: Introductionmentioning
confidence: 98%
“…In addition, there are also some other methods to estimate the minimum variance, such as the processes and disturbances completely identification method, the filtering and correlation analysis method [21], the recursive least squares method [22]. With the estimation of the minimum variance, the upper bound of the MIE can be obtained by (17).…”
Section: H Min Estimationmentioning
confidence: 99%
“…Thus the generalized models of the lifted DR rate and SSR rate can be obtained from (10) and (12). For the FSR, DR and SSR control loops, we design the optimal controllers, calculate the minimum cost functions and then do simulations.…”
Section: Examplementioning
confidence: 99%
“…It is known that the minimum variance (MV) control is the best possible control in the sense that no controllers can provide a lower variance for linear systems with time delays. Many papers [9][10][11][12][13] have shown that MV is a useful benchmark to assess control-loop performance. A significant one is Reference [9] which presented a new direction and framework for the control-loop performance-monitoring area.…”
Section: Introductionmentioning
confidence: 99%